The Land–Water–Energy Nexus of Ruzizi River Dams (Lake Kivu Outflow, African Great Lakes Region): Status, Challenges, and Perspectives - Muvundja, Fabrice Amisi; Walumona, Jacques Riziki; Dusabe, Marie-Claire; Alunga, Georges Lufungula; Kankonda, Alidor Busanga; Albrecht, Christian; Eisenberg, Joachim; Wüest, Alfred (Frontiers in Environmental Science, 2022)
Hydropower (HP) dam is the main source of electricity in Africa, including the Democratic Republic of Congo. The need for constructing new dams is even higher than ever. However, the new HP dams should further comply with environmental-friendly benefiting requirements. River systems need water to maintain their hydraulic and ecological functions. Flow regime disturbance is an environmental risk that may prevent rivers from providing their ecosystem services to the riparian populations. Unfortunately, most of the dammed African rivers are understudied regarding their environmental flow requirements. This study analysed the hydrological regime and water quality of the Ruzizi River. We aimed at estimating the minimum water flow at Ruzizi I HP dam and at land management constraints to cope with electricity production and river ecological integrity while minimizing the effects of hydropeaking. According to Gumbel’s hydrological model, the discharge of ~130 m3/s showed the longest return period (12 years) among the most recurrent flows. In contrast, the maximum recorded discharge of 143 m3/s showed a return time of 76 years. Any discharge comprising between 46 and 120 m3/s could occur at any time within three years. A possible minimum environmental flow of 28 m3/s (i.e., 25%) was derived from the discharge-hydropower production relationship of the power plant. The water quality for drinking purposes was assessed using the water quality index (WQI) method based on WHO standards. Turbidity (i.e. total suspended solids) upstream and downstream the dams were highly correlated to rainfall (r = 0.8; n = 12) and land use. This indicated a more important reservoir siltation at Ruzizi I than at Ruzizi II Water quality assessment reveals that the Ruzizi River is currently unsuitable for drinking water purpose because WQI values exceed the WHO drinking water standards. Therefore, the Ruzizi River waters must be categorized as “unsuitable” for this purpose.